Analisis Lingkungan Kerja dan Motivasi Kerja Terhadap Kinerja Perawat pada Rumah Sakit Al-Fatah Ambon - Fitria Mahu; Farida Mony; A. R Latuconsina (Lembaga Intelektual Muda (LIM) Maluku, 2022)
The purpose of this study was to determine and analyze the influence of the Work Environment and Work Motivation on the Performance of Nurses at Al-Fatah Hospital Ambon. The analytical tool used in this study was multiple linear regression. The population of 35 people or all nurses at Al-Fatah Hospital Ambon, which was sampled in this study was 35 nurses at Al-Fatah Hospital Ambon. The results showed that the independent variables Work Environment (X1) and Work Motivation (X2), have a positive and significant influence on the dependent variable, namely Nurse Performance (Y), this means that the work environment and work motivation that employees feel will have an impact on the performance of nurses at Al-Fatah Hospital Ambon. The dominant influence is the Work Environment variable